2023
DOI: 10.1002/eji.202350394
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic use during pregnancy is linked to offspring gut microbial dysbiosis, barrier disruption, and altered immunity along the gut–lung axis

Abstract: Antibiotic use during pregnancy is associated with increased asthma risk in children. Since approximately 25% of women use antibiotics during pregnancy, it is important to identify the pathways involved in this phenomenon. We investigate how mother‐to‐offspring transfer of antibiotic‐induced gut microbial dysbiosis influences immune system development along the gut–lung axis. Using a mouse model of maternal antibiotic exposure during pregnancy, we immunophenotyped offspring in early life and after asthma induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Now, decades later, both epidemiological observations and proof‐of‐concept animal models have demonstrated the substantial effect that the early‐life environment has on fetal and neonatal development 3,4 . In addition to nutrition, many studies have identified other environmental influences during pregnancy that play a major role in offspring development and overall health including (but not exhaustive): antibiotic use during pregnancy, 5–7 maternal immune activation, 8–10 stress, 11,12 and vaginal microbiome exposure 13 . This research has provided a framework for the Developmental Origins of Health and Disease Hypothesis (DOHaD), 3,14,15 which states that environmental cues present during critical perinatal time points developmentally program offspring organ systems and subsequently influence individual health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Now, decades later, both epidemiological observations and proof‐of‐concept animal models have demonstrated the substantial effect that the early‐life environment has on fetal and neonatal development 3,4 . In addition to nutrition, many studies have identified other environmental influences during pregnancy that play a major role in offspring development and overall health including (but not exhaustive): antibiotic use during pregnancy, 5–7 maternal immune activation, 8–10 stress, 11,12 and vaginal microbiome exposure 13 . This research has provided a framework for the Developmental Origins of Health and Disease Hypothesis (DOHaD), 3,14,15 which states that environmental cues present during critical perinatal time points developmentally program offspring organ systems and subsequently influence individual health outcomes.…”
Section: Introductionmentioning
confidence: 99%